DIGITAL ECONOMY (Conferencea, 2023)
The digital economy is growing fast, especially in developing countries. Yet the meaning and metrics of the digital economy are both limited and divergent. The aim of this paper is to review what is currently known in order to develop a definition of the digital economy, and an estimate of its size. The paper argues there are three scopes of relevance. The core of the digital economy is the ‘digital sector’: the IT/ICT sector producing foundational digital goods and services. The true ‘digital economy’ – defined as “that part of economic output derived solely or primarily from digital technologies with a business model based on digital goods or services” – consists of the digital sector plus emerging digital and platform services. The widest scope – use of ICTs in all economic fields – is here referred to as the ‘digitalised economy’. Following a review of measurement challenges, the paper estimates the digital economy as defined here to make up around 5% of global GDP and 3% of global employment. Behind this lies significant unevenness: the global North has had the lion’s share of the digital economy to date, but growth rates are fastest in the global South. Yet potential growth could be much higher: further research to understand more about the barriers to and impacts of the digital economy in developing countries is therefore a priority.